Changes over Time in the Revenue-Expense Relation: Accounting or Economics? - Donelson, Dain C.; Jennings, Ross; McInnis, John (The Accounting Review, 2011)
ABSTRACT: Dichev and Tang (2008) document a dramatic decrease over the last 40 years in the contemporaneous correlation between revenue and expense, along with an associated increase in earnings volatility and a decline in earnings persistence, suggesting a decline in earnings quality. We document that these changes are primarily attributable to an increase in the incidence of large special items. We then examine the extent to which this increase in special items is due to either more frequent real economic events related to special item recognition or to the adoption of new accounting standards. Our evidence suggests that changes in the frequency of economic events associated with special items have played a more important and sustained role relative to the role played by adoption of individual accounting standards. Finally, we find that the changing incidence of these economic events is at least in part related to the well-documented increase in competition in the U.S. economy over the last four decades.